ANALISIS ELEMEN-ELEMEN BRAND EQUITY RUMAH SAKIT PKU MUHAMMADIYAH GOMBONG - Hasnah Rimiyati; Diana Astuti (Universitas Muhammadiyah Yogyakarta, 2012)
Increasing competition in hospital, which in the view of many private hospitals are well established in Gombong, PKU Muhammadiyah Gombong hospitals must have a strong brand equity to maintain or retain old customers and interesting new customers. Research is important conducted to determine and analyze ratings and views of customer on the hospital, other than research about brand equity in the hospital still rarely done. To know the views of consumers on brand awareness, brand association, perceived quality and brand loyalty PKU Muhammadiyah Gombong Hospitals. The study was quantitative descriptive design. The study was conducted on 25 February - 3 June 2011 in the region Gombong. Population are all community Gombong had ever feel the services PKU Muhammadiyah Gombong Hospital. Number of sample was 100 respondents. Sampling design used was purposive sampling. Analysis of data used descriptive statistics, Cochran's test, the average value, semantic differential scale and importance vs. performance comparison PKU Muhammadiyah hospitals as a top of mind awareness Gombong society. Based on calculations by the Cochran test at the brand association, there are 9 associations are closely related. Based on the results of the analysis of perceived quality, there are seven attributes of a good scale range (3.40 to 4.20) and 3 attributes entered enough scale range (2.60 to 3.40). Analysis of brand loyalty found: Switcher buyers equal to 23%, category simply (3.01). Habitual buyers is equal to 55%, both categories (3.44). Satisfied buyer equal to 49%, both categories (3.46). Liking the brand equal 43%, both categories (3.51). Commited buyers by 33% and include enough category (2.79) PKU Muhammadiyah Gombong Hospitals have a strong enough brand equity.